Open-book accounting no relacionamento entre cooperativa e cooperados no setor cafeeiro - Lima, Daiane da Silva (2022)
Coffee has an expressive role on Brazil´s economy, cooperatives are essential on coffee business in the country. The interconnected relationships between organizations are getting more and more important each day in a connected economy, it brings all organizations closer, especially the cooperatives. The tight relationship causes the evolution and adoption of new technics of costs management, which goes beyond the company standard limits, for example the Open-book Accounting (OBA). That been said. The study targets, are analyzing how OBA´s is conducted, considering their dimensions, based on the relationship between the cooperatives and its partners, focusing on the perspective savings on transactions costs. That work was made through a study of a cooperative and its associates, and partners. To collect data, were used interviews, documents and data analysis, and direct observation without any intervention. The technique used to analyze data and documents was content analysis (CA). It was observed in the study the use of bilateral with no limited of exchanging information, which was very detailed when it was send partners to cooperative, and low detailed when it was from cooperative to partners. It was possible noticing that both cooperatives and partners were looking for their own personal interests, even tough, the growth of one is interesting to one another, makes the relationship based in trust and cooperation, providing several incentives. It was also observed, that the cooperative uses the information obtained from the partners, to plain their future activates, and control the quality of the coffee produced by them, that will be received. And the partners use that information to identify mutual commitment by the cooperative, ensure trust and identify the value of the leftover which they have an annual right to receive. It was also figured that the transactions costs weren´t zero, but they are reduced, observing that both partners and cooperative do not realize the opportunism of using the shared data. Summarizing, the relationship between cooperatives and partners are favorable to the use of the OBA, once the relationship is based in cooperation, which is the main foundation for its application and use, and achieves potential bilateral benefits. It can sometimes be tension in the relationship, but also shows that there are no ``different poles`` in this type of relation, seen that the objective of a creation of a cooperative is the voluntary entry of its members, and the assistance on managing their business and selling their products. This survey contributes to literature, amplifying the knowledge in areas such as business administration and accountability, when it talks about OBA, and showing, the strong and weak points about exchange of information on costs, processing and other activities used on cooperative´s activities, that can be useful to cooperatives and its associates, but also to another relevant fields on business world. The survey yet shows a social contribution, because when it demonstrates a adequate management of costs based on relation cooperative-partners, the partners business should present superior performance, reflecting directly on the activities maintenance, and as well bringing Incoming to the families involved in the process.